Rethinking Religious Pluralism in Qur'anic Interpretation: A Multicultural Reading of Imam Basyari - Fadhila Sidiq Permana; Sahiron Syamsuddin (UIN Raden Mas Said Surakarta, 2026)
Indonesia is a multicultural nation characterized by religious diversity, including Islam, Christianity, Catholicism, Buddhism, Hinduism, and Confucianism. This diversity has long been sustained through the national principle of Bhinneka Tunggal Ika (Unity in Diversity). Nevertheless, religiously motivated conflicts continue to occur, often resulting from exclusive interpretations of religious teachings and discriminatory attitudes toward other faith communities. This study examines Imam Basyari’s interpretation of Qur’an 2:62 (QS. al-Baqarah [2]: 62) and evaluates its relevance to contemporary issues of religious pluralism and interreligious relations in Indonesia. Employing a library research method and a multicultural philosophy approach, the study critically analyzes Imam Basyari’s exegetical perspective on religious diversity. The findings reveal that although Imam Basyari’s interpretation seeks to affirm Islamic theological principles, several aspects of his interpretation require further reexamination in light of multicultural values and contemporary social realities. The study argues that a more inclusive reading of the verse can contribute to fostering social cohesion, reducing interreligious tensions, and promoting mutual recognition among diverse religious communities. This research contributes to Qur’anic studies by offering a critical reassessment of Imam Basyari’s interpretation through the lens of multicultural philosophy.